PERSEPSI PESERTA DIDIK KELAS VI SD IT BUDI MULYO TERHADAP ARTIFICIAL INTELLIGENCE (AI) SEBAGAI MEDIA PEMBELAJARAN EDUKATIF - Nasicha Qairo Riyani; Muhammad Riza Dewantara; Yulia Palupi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to explore students' responses to the use of Artificial Intelligence (AI) in elementary school learning. The research method employed was a survey involving 25 elementary school students. Data collection was conducted using a questionnaire comprising 10 items, distributed offline via printed copies. The results of the study indicate that students agreed with the use of AI, felt comfortable utilizing AI to seek information, and expected teachers to incorporate AI tools into learning activities. The implications of this research highlight that integrating AI technology into elementary school learning has the potential to enhance students' learning experiences. Therefore, it is recommended to provide training for teachers on the use of AI technology in education, as well as to develop supporting technological infrastructure within educational environments. Consequently, these collective efforts will support the achievement of inclusive, innovative, and sustainable learning goals in elementary schools.